The Impact of Polyphenol on General Nutrient Metabolism in the Monogastric Gastrointestinal Tract - Mohammed Sharif Swallah; Hongling Fu; He Sun; Raïfatou Affoh; Hansong Yu (Journal of Food Quality)
Polyphenols are bioactive compounds occurring in plant foods, which are considered significant owing to their contribution to human health and the prevention of chronic diseases. Phenolic compounds mainly depend on plant food structure and the interaction with other food constituents, mostly proteins, lipids, and carbohydrates. The interaction with the food matrices can obstruct or enhance nutrient accessibility and availability and even impair others. Food digestion is a complex process where ingested foods are converted to nutrients via mechanical and enzymatic alterations. The absorption of nutrients predominantly occurs in the small and large intestine, respectively. The metabolised product, however, is the main bioactive component due to their ability to enter the systemic circulation and reach the targeted organs. There is limited knowledge on the cellular uptake, phenolic metabolite, and polyphenolic effect in the gastrointestinal ecosystem. Therefore, improved understanding of the biological properties and stages of dietary phenols is essential for the effective utilization of their therapeutic potentials. This review will explore, summarise, and collate current information on how polyphenols influence nutrient metabolism, bioavailability, and the biotransformation stages.